(untitled) (Research, Society and Development, 2022)
Understanding the perception of pregnant women reported with syphilis or who had children exposed or reported with Congenital Syphilis about prenatal care is extremely important for improving the care offered by the health service. Methods: This is a descriptive, cross-sectional, analytical study, with a qualitative approach, carried out in the city of Floriano, Piauí, covering the years 2016 to 2020. 24 cases of pregnant women with Syphilis were identified, of which only 10 agreed to participate of the interview. Of the participants, 07 reported being in a stable union, with only 03 single. Regarding education, 05 had completed elementary school, and 5 had completed high school. Family income of up to one minimum wage was reported by all women, working only in domestic services and/or in their homes. The study allowed a deeper analysis in relation to the feeling and meanings of syphilis for pregnant women. As well as the service and care performed and offered. Most of the interviewees performed the test for the detection of syphilis and had no difficulty with the treatment, as well as the support of the partner.